2022
DOI: 10.1002/ptr.7383
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide protects against alcohol‐induced liver injury by regulating gut microbiota, oxidative stress and attenuating inflammation in vivo and in vitro

Abstract: Costunolide (cos) derived from the roots of Dolomiaea souliei (Franch.), which belongs to the Dolomiaea genus in the family Compositae, exert the anti-inebriation effect mainly by inhibiting the absorption of alcohol in the gastrointestinal tract. However, the protective effect of cos against alcohol-induced liver injury (ALI) remains obscure.The present study was aimed to evaluate the hepatoprotective effects of cos (silymarin was used as positive control) against ALI and its potential mechanisms. MTT was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…It has been reported that Cos administration decreased doxorubicin-induced cardiorenal injury by suppressing oxidative stress [31]. In another study, Cos attenuated alcohol-induced liver injury by reducing ROS production [32]. Interestingly, Cos obviously increases the intracellular oxidative stress in human U2OS cells and promotes the generation of ROS in esophageal cancer cells, and eventually induces apoptosis of carcinoma cells [33].…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that Cos administration decreased doxorubicin-induced cardiorenal injury by suppressing oxidative stress [31]. In another study, Cos attenuated alcohol-induced liver injury by reducing ROS production [32]. Interestingly, Cos obviously increases the intracellular oxidative stress in human U2OS cells and promotes the generation of ROS in esophageal cancer cells, and eventually induces apoptosis of carcinoma cells [33].…”
Section: Discussionmentioning
confidence: 93%
“…RAW264.7 macrophages were seeded into 96-well plates at a density of 5 × 10 3 cells per well and cultured for 24 h. Then, cells were pretreated with OE (80 μg/mL) for 3 h, and LPS (1 μg/mL) was subsequently added and cultured for the indicated time. Immunofluorescence staining was performed as per our previous report [ 12 ]. Images were captured at 400× magnification with confocal mode by Operetta CLS High Content Analysis System (PerkinElmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One of the naturally occurring sesquiterpene lactones is costunolide, which has been extensively investigated for a wide range of biological activities. A study found that costunolide treats ALD by modulating oxidative stress and reducing inflammation in vivo and in vitro , which is inseparable from its impact on the gut microbiota ( 30 ). Coprinus Comatus polysaccharide, a polysaccharide extract of the edible mushroom species Coprinus Comatus, has been shown to exert prebiotic-like effects to increase gut microbiota diversity, which might improve adverse changes in gut microbiota caused by alcohol consumption and delay ALD progression ( 31 ).…”
Section: Targeting Gut Microbiota For Aldmentioning
confidence: 99%